2014
DOI: 10.15253/2175-6783.2014000600012
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ quality of life

Abstract: One aimed to evaluate the quality of life of nursing students from a public university from Dourados, MS, Brazil. This is an exploratory, descriptive and cross-sectional study conducted in October and November 2011 through the demographic and quality of life questionnaires SF-36. Out of the 102 students who participated in the study, 91.0% were between 18 to 23 years old, 49.01% had financial support from their parents of up to two minimum wages, 89.5% were single, 98.7% did not work. Nursing students from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
4
0
5
Order By: Relevance
“…Several studies show that, as the research "Quality of life of nursing students", in which women also predominated, with 82.4%. 10 According to shifts, we observed that most students study in the morning. However, in the last semester, especially in internships, these classes mix, so that students study in both shifts or reconcile their grid according to their routine, in the morning or afternoon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that, as the research "Quality of life of nursing students", in which women also predominated, with 82.4%. 10 According to shifts, we observed that most students study in the morning. However, in the last semester, especially in internships, these classes mix, so that students study in both shifts or reconcile their grid according to their routine, in the morning or afternoon.…”
Section: Resultsmentioning
confidence: 99%
“…There was also a negative impact in the wellbeing perception, which is greater in students from the last year of the course in relation to students from previous years. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) This study allowed identifying that, throughout the nursing course, students face various moments and situations, which may or may not be favorable to the promotion of their quality of life. Graduation is a remarkable moment in the student's life, because this stage defines him/her as a person and professional.…”
Section: Resultsmentioning
confidence: 99%
“…The study's results highlight the prevalence of the female gender among the Nursing students, which denotes preliminary characteristics on certain aspects of the Nursing graduation profile, already noted in the literature. 19 There was also predominance of Nursing students in the young age group, data corroborated by a study carried out with university Nursing students who assisted to a public university in the inland of Piauí. 20 The majority of students mentioned they came from Teresina/PI, contrary to the findings of another research carried out in Montes Claros/MG, where students, in their majority, were born and lived in the city were they study.…”
Section: Discussionmentioning
confidence: 59%
“…Em relação aos hábitos não saudáveis, como alimentação desequilibrada, sono prejudicado e relações sociais e familiares alteradas, estes são ocasionados devido aos compromissos acadêmicos, o que produz ansiedade, estresse e baixa autoestima. Resultado similar, em uma Universidade Estadual de Mato Grosso do Sul, também apontou que o envolvimento nos compromissos acadêmicos ocasiona ansiedade e estresse entre os estudantes (4) . O estresse é um fator nocivo à saúde mental e ao bem-estar físico, estando associado a doenças como as cardiovasculares, câncer e distúrbios gastrointestinais, assim como depressão, padrões de sono ruins e incapacidade de realizar atividades diárias eficazes (7) .…”
Section: Discussionunclassified
“…Ao adentrar na universidade, o estudante, em sua maioria jovem, encontra-se em fase de transição para a vida adulta, trazendo consigo várias inseguranças, como a sua adaptação à academia, a ansiedade de satisfazer as expectativas sociais e familiares, e no decorrer dos estudos o estresse com as muitas atividades e compromissos acadêmicos, o que será enfrentado de forma relativa à maturidade psicológica de cada um. Assim sendo, toda essa nova rotina pode trazer desgastes físicos e mentais, comprometendo, desse modo, a sua aprendizagem (4) . Nesse sentido, a enfermagem, corpo profissional que estabelece maiores relações com as pessoas, em que seu cuidado está intrinsecamente relacionado ao seu bem-estar e promoção da saúde, deve capacitar os estudantes para a adoção de escolhas saudáveis, tendo em vista o impacto dessas escolhas no surgimento de problemas, por exemplo, o seu rendimento acadêmico, diminuição do absenteísmo, dentre outros que circundam esse contexto (5) .…”
Section: Introductionunclassified